Nosocomial infection prevalence in patients undergoing extracorporeal membrane oxygenation (ECMO): protocol for a point prevalence study across Australia and New Zealand - John F Fraser; Rachael Parke; Amanda Corley; India Lye; Jayshree D Lavana; Abhilasha Ahuja; Chris M Anstey; Paul Jarrett; Emma Haisz; Vincent Pellegrino; Hergen Buscher (BMJ Open)
Introduction Extracorporeal membrane oxygenation (ECMO) provides cardiac and/or respiratory support when other therapies fail. Nosocomial infection is reported in up to 64% of patients receiving ECMO and increases morbidity and mortality. These patients are at high risk of infection due, in part, to the multiple invasive devices required in their management, the largest being the cannulae through which ECMO is delivered. Prevalence of nosocomial infection in ECMO patients, including ECMO cannula-related infection, is not well described across Australia and New Zealand.Methods and analysis This is a prospective, observational point prevalence study of 12 months duration conducted at 11 ECMO centres across Australia and New Zealand. Data will be collected for every patient receiving ECMO during 12 predetermined data collection weeks. The primary outcome is the prevalence of laboratory-confirmed bloodstream infection, and suspected or probable nosocomial infections; and the secondary outcomes include describing ECMO cannula dressing and securement practices, and adherence to local dressing and securement guidelines. Data collection will be finalised by March 2019.Ethics and dissemination Relevant ethical and governance approvals have been received. Study results will describe the prevalence of suspected and confirmed nosocomial infection in adult, paediatric and neonatal patients receiving ECMO across Australia and New Zealand. It is expected that the results will be hypothesis generating and lead to interventional trials aimed at reducing the high infection rates seen in this cohort. Results will be published in peer-reviewed journals and presented at relevant conferences.Trial registration number ANZCTRN12618001109291; Pre-results.